What's Wrong With Research Literatures? And How to Make Them Right - Howard, G; Hill, T; Maxwell, SE; Baptista, T; Farias, M; Coelho, C; Coulter-Kern, M; Coulter-Kern, R (2009)
Meta-analysis is now the accepted procedure for summarizing research literatures in areas of applied psychology. Because of the bias for publishing statistically significant findings, while usually rejecting nonsignificant results, our research literatures yield misleading answers to important quantitative questions (e.g., How much better is the average psychotherapy patient relative to a comparable group of untreated controls? How much more aggressive are children who watch a great deal of violent TV than children who watch little or no violence on TV?). While all such research literatures provide overly optimistic meta-analytic estimates, exactly how practically important are these overestimates? Three studies testing the literature on implementation intentions finds only slightly elevated effectiveness estimates. Conversely, in three studies another growing research literature (the efficacy of remote intercessory prayer) is found to be misleading and is in all likelihood not a real effect (i.e., our three studies suggest the literature likely consists of Type I errors). Rules of thumb to predict which research literatures are likely invalid are offered. Finally, revised publication and data analysis procedures to generate unbiased research literatures in the future are examined. © 2009 American Psychological Association.